Micropropagation of Rubus chrysophyllus Reinw. ex Miq. and Rubus fraxinifolius Poir. - Lily Ismaini; Destri Destri; Muhammad Imam Surya (Journal of Tropical Life Science, 2017)
Rubus chrysophyllus and Rubus fraxinifolius are a native species in Indonesia, which has highly potential to be developed as fruits crops. Propagation is an important factor in developing a fruit cultivation. In vitro micropropagation is an important instrument to improve the quality of seedling. Our experiment was aimed to study the micropropagation of R. chrysophyllus and R. fraxinifolius. The shoot tips were cultured on MS medium supplemented with 10 mg/L indole-3-butyric acid (IBA) for enhancing roots of R. chrysophyllus and R. fraxinifolius in the in vitro condition. Then, the rooted plantlets were transplanted into cocopeat media for acclimatization. The results showed that R. chrysophyllus and R. fraxinifolius gave a different response on the medium contain 10 mg/L of IBA. The R. fraxinifolius shows the best results compared to R. chrysophyllus on 14 days after subculture. The roots length and roots numbers of R. fraxinifolius and R. chrysophyllus were 9.13 cm and 11.25; 2.20 cm and 2.00, respectively. Although R. fraxinifolius was growing better than R. chrysophyllus, but after acclimatization R. chrysophyllus were able to grow faster than R. fraxinifolius. Moreover, on the parameters of plant height shows that R. chrysophyllus (9.20 cm) were growth higher than R. fraxinifolius (4.05 cm) during acclimatization.